Colombia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to the Colombian economy. Despite adverse global circumstances, Colombia's successful policies and inclusive growth agenda continued in 2015. Colombia's strong policy framework helped ensure an orderly adjustment to the deteriorated external conditions. Although the medium-term outlook is favorable, it is surrounded by downside risks. The main near-term risks stem from Colombia's still significant near-term external financing needs and potential capital inflow reversals, the result of volatile global financial conditions. On the upside, bringing the peace process to fruition could further improve business confidence and capital inflows, reinforcing the recovery that will follow the necessary adjustment process.